The relationship between education level, occupation, income and parity with efforts to manage symptoms in menopausal women in Banguntapan Urban Village Yogyakarta - Mawardani, Siti; Sariyati, Susiana; Wijayanti, Indah (Alma Ata University Press, 2025)
Background: Menopause is the stage when a woman has not experienced menstruation for 12 consecutive months. A woman is considered to reach menopause when the FSH level in the blood exceeds 40 mIU/ml and the estradiol level is below 30 pg/ml. According to WHO, menopause is the permanent cessation of menstrual cycles caused by the loss of ovarian follicle activity and 12 continuous months of amenorrhea. Menopause complaints in women can include hot flashes, insomnia, dizziness, night sweats, constant headaches, joint pain, feelings of pressure for no reason, pain during intercourse, osteoporosis, vaginal dryness, decreased function of the reproductive system, muscle weakness, breasts that are no longer firm, increased risk of heart disease. The changes in psychological disorders are worry, fear, repetitive thinking, excessive vigilance, anxiety and depression. Changes during menopause include changes in the decrease in the hormones estrogen and progesterone from the ovaries. If the symptoms above are not treated, they can disrupt daily life and never make efforts to deal with the complaints experienced.Objective: This study aims to determine the relationship between menopause characteristics and symptom management efforts in menopausal women.Methods: This research was conducted using a quantitative approach with a cross-sectional design, using purposive sampling technique and primary data in Banguntapan Village, data analysis techniques using Chi Square statistical tests.Results: The number of respondents who have high education and low education is balanced, namely 72 respondents (50.0%), more respondents who have more than one child (multigravida), namely 116 (80.6%), the number of respondents who do not work is 78 (54.2%), the majority of lower income, namely 118 respondents (84.7%), more respondents who have good handling efforts, 128 respondents (88.9%).Conclusion: The results of the Chi-square test (x2) indicate a significant relationship between education level and symptom management efforts, as evidenced by a p-value of 0.008, which is less than the significance level of 0.05. On the other hand, no significant relationship was found between parity and symptom management efforts, with a p-value of 0.941, which is greater than 0.05. Similarly, there is no significant relationship between employment status and symptom management efforts, as the p-value was 0.721 (>0.05). Additionally, the study found no significant relationship between socioeconomic status and symptom management efforts, with a p-value of 0.137 (>0.05)